2020
DOI: 10.2334/josnusd.19-0218
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and histological evaluations of alveolar ridge augmentation using a novel bi-layered porous polyethylene barrier membrane

Abstract: Guided bone regeneration (GBR) is an effective alveolar ridge reconstruction technique used before or at implant placement. The combination of various barrier membranes and bone substitutes has been employed. This study aimed to perform a preliminarily evaluation of the safety and performance of a new nonabsorbable bi-layered porous polyethylene (PPE) membrane, in combination with a freeze-dried cortical bone allograft in posterior mandibular ridge augmentation. Fifteen adults who had combined posterior mandib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…(Table 2). Twenty one studies recruited participants based on specific restrictions in terms of smoking habits (excluded all current smokers 42,50,56,60,62,64,65 ; smokers who smoked >10 cigarettes a day 46,47,51–53,61,63,66,68 ; >15 cigarettes a day 40 ; >19 cigarettes a day 17 ; >20 cigarettes a day 43,44,49 ). Nineteen studies recruited participants based on specific exclusion criteria based on periodontal disease status or oral hygiene (excluded patients with full mouth plaque score and bleeding score ≥ 20% 17 ; >25% 51,52,61 ; poor oral hygiene 42,63 ; active or uncontrolled periodontal disease 40,45–47,50,53,55,56,60,65,66,68 ), and two studies had participants with periodontitis undergo periodontal therapy prior to any GBR procedure or implant placement 41,55 …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…(Table 2). Twenty one studies recruited participants based on specific restrictions in terms of smoking habits (excluded all current smokers 42,50,56,60,62,64,65 ; smokers who smoked >10 cigarettes a day 46,47,51–53,61,63,66,68 ; >15 cigarettes a day 40 ; >19 cigarettes a day 17 ; >20 cigarettes a day 43,44,49 ). Nineteen studies recruited participants based on specific exclusion criteria based on periodontal disease status or oral hygiene (excluded patients with full mouth plaque score and bleeding score ≥ 20% 17 ; >25% 51,52,61 ; poor oral hygiene 42,63 ; active or uncontrolled periodontal disease 40,45–47,50,53,55,56,60,65,66,68 ), and two studies had participants with periodontitis undergo periodontal therapy prior to any GBR procedure or implant placement 41,55 …”
Section: Resultsmentioning
confidence: 99%
“…All but two studies reported on the mean age or age range of the participants. 51,60 Five randomized clinical trials, 39,41,42,44,45 one prospective cohort study, 47 and six case series 17,57,60,62,63,66 were registered and approved by an ethics committee.…”
Section: Description Of Selected Studiesmentioning
confidence: 99%
See 3 more Smart Citations